Gene Mutational Clusters in the Tumors of Colorectal Cancer Patients With a Family History of Cancer - Huang, He; Deng, Ting; Guo, Yuntong; Chen, Hao; Cui, Xiaolong; Duan, Jingjing; Yang, Yuchong; Guo, Zhixin; Ba, Yi (Frontiers in Oncology, 2022)
Introduction: Family history is a high-risk factor for colorectal cancer (CRC). The risk comes not only from known hereditary mutations but also unknown family mechanisms causing somatic mutations. Uncovering the family unknown mechanisms would be an important step to improve the diagnosis and treatment of these families. Method: Samples from 168 patients with advanced CRC were collected and applied to next-generation sequencing of 624 pan-cancer genes. Genomic mutations and significantly mutated genes were called. Significantly mutated genes and co-mutated genes were used to cluster patients. By each cluster of patients, mutational signatures were extracted. The identified patient cluster was further validated in another independent dataset. Result: Significantly mutated genes including TP53, APC, KRAS, and SMAD4 were found associated with tumor mutation burden and microsatellite instability. LRP1, ACVR2A, and SETBP1 were found co-mutated. Patients with mutations in LRP1, ACVR2A, and SETBP1 tend to have a family history of cancer than others. Those patients were more likely of right-sidedness, high tumor mutation burden, and microsatellite instability. The signature analysis identified two possible etiologies, SBS10a (defective polymerase epsilon exonuclease domain) and SBS6 (defective DNA mismatch repair and microsatellite unstable tumors). Conclusion: The identified gene cluster (LRP1, ACVR2A, and SETBP1) could be a good biomarker of these patients with a family risk, which was characterized by right-sidedness, high mutation burden, and high microsatellite instability.